Analysis of Service Quality in Enhancing Customer Satisfaction at Jamil Sembako Store in Kaliwulu, Plered, Cirebon - In’amul Hasan; Heru Cahyono; Mawar Jannati Al Fasiri; Gama Pratama (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This research aims to find out about service quality analysis in increasing consumer satisfaction at the Jamil grocery store in Kaliwulu Plered Cirebon. The theoretical view of service quality consists of 5 concrete dimensions, the reliability dimension, the responsibility dimension, the security dimension, and finally the empathy dimension. This research method is descriptive qualitative, namely an approach to a particular phenomenon, behavior, event or situation which is the object of research. Data collection techniques in this research are interview techniques, observation techniques, and documentation techniques. Based on the research results, it can be concluded that the service provided by Jamil store employees is quite good. Judging from the results of interviews with informants who said that the shop employees were quite quick and polite and correctly carried out the 3S (smile, greet, greeting), serving painstakingly quickly and precisely